Novel Assay to Measure Seroprevalence of Zika Virus in the Philippines - Cameron Adams (Centers for Disease Control and Prevention, 2021)
Zika virus (ZIKV) is a member of the Flaviviridae family, which includes other clinically notable viruses such as the 4 dengue virus serotypes (DENV-1–4). Distinguishing DENVs from ZIKV using the established serologic assays widely used for monitoring DENV transmission is difficult because of antibody cross-reactivity between these closely related flaviviruses. We describe a modified and improved recombinant envelope domain III–based serologic assay for detecting ZIKV type-specific antibodies in regions with endemic DENV transmission. When the assay was used to measure ZIKV seroprevalence in 2017 among children 9–14 years of age living in a region of the Philippines with endemic DENV transmission, we observed a ZIKV seroprevalence of 18%. Investigators should consider using the ZIKV envelope domain III–based assay, which is simple and readily adaptable for use in standard clinical and public health laboratories, to assess ZIKV seroprevalence in areas with endemic DENV transmission.